Effect of Thermal Mitigation on Porcine Epidemic Diarrhea Virus (PEDV)- Contaminated Feed - R. A. Cochrane; L. L. Schumacher; S. S. Dritz; J. C. Woodworth; A. R. Huss; C. R. Stark; J. M. DeRouchey; M. D. Tokach; R. D. Goodband; J. Bai; Qi Chen; Jianqiang Zhang; et al. (Kansas Agricultural Experiment Station Research Reports, 2015)
Porcine Epidemic Diarrhea Virus (PEDV) is primarily transmitted by fecal-oral contamination. However, epidemiological evidence has shown that swine feed and ingredients may serve as potential vectors of transmission. Since it is known that PEDV is a heat-sensitive virus, we hypothesized that a conditioner and pellet mill mimicking commercial thermal processing would mitigate PEDV infectivity. To test this hypothesis, two experiments were designed to determine if different pellet mill conditioner retention times or temperatures would impact PEDV infectivity determined by polymerase chain reaction (PCR) analysis and bioassay. For the first study, a 3×3×2 factorial was utilized, with three pelleting temperatures (155, 175, or 195°F), three conditioning times (45, 90, or 180 s), and two levels of virus (low: 1×102TCID50/g, or high: 1×104TCID50/g). Non-inoculated and PEDV-inoculated unprocessed mash were used as controls. There was no PEDV RNA detected in the PEDV-free mash. The low-dose PEDV-infected mash was 6.8 ± 1.8 cycle threshold (Ct) greater (P<0.01) than the high dose mash. Regardless of time or temperature, feed processing increased (P<0.01) the Ct compared to the PEDV-inoculated unprocessed mash. As expected, fecal shedding of PEDV was not detected in rectal swabs from control pigs for the duration of the study. Fecal swabs from pigs fed the PEDV-inoculated unprocessed mash, regardless of dose, were PEDV-positive from 2 to 7 days post-inoculation, at which time the pigs were sacrificed. However, if either PEDV dose of inoculated feed was pelleted at any of the nine tested conditioning time × temperature combinations, no PEDV RNA was detected in fecal swabs or cecum content. Based on these results, a second experiment was developed to determine the impact of lower processing temperatures on PEDV infectivity. The pellet mill was heated for 1 hour at normal manufacturing conditions prior to simulating a plug by turning off the steam supply. This allowed the temperature of the mash feed to decrease below 100°F. The PEDV-inoculated feed was then pelleted at one of five conditioning temperatures (100, 115, 130, 145, or 160°F) for 30 s. This study was repeated three times on three separate days with complete decontamination between each experiment day. Again, non-inoculated and PEDV-inoculated mash were used as controls. The five increasing temperatures led to feed with respective mean Ct values of 32.5, 34.6, 37.0, 36.5, and 36.7. Even though all samples had detectable PEDV RNA in the feed, infectivity was only detected by bioassay in pigs from the 100 and 115°F conditioning treatments. In each of the other processing temperatures, no PEDV RNA was detected in fecal swabs or cecum contents. Our results suggest that processing feed through a conditioner and pellet mill similar to those used in commercial feed mills will be effective as a point-in-time mitigation step for PEDV as long as conditioning temperatures remain above 130°F. Any time feed is processed at temperatures below that level, such as during start-up or when the pellet mill die becomes plugged and the steam is consequently shut off, there is a risk that the feed can act as a vector for transferring infectious PEDV and lead to cross-contamination of post-pelleting handling equipment.
Keywords: feed safety; PEDV; thermal mitigation; swine